Ocular Diseases - Adio, Adedayo (IntechOpen, 2012)
This comprehensive resource on ocular diseases will provide you with a better and more practical understanding of the science behind eye disease and help you to relate it with treatment. Some of the contributors to this book are some of the world's leading and most experienced scientists in this major area of interest and they have provided great insight into this often difficult to understand aspect of ophthalmology. Its unique blend of basic science and clinical applications will serve you as a clinical guide to understanding the cause and management of ocular disease.